Cardiovascular Disease Burden and Socioeconomic Correlates: Findings From the Jackson Heart Study. Issue 8 (August 2017) - Min, Yuan‐I; Anugu, Pramod; Butler, Kenneth R.; Hartley, Tara A.; Mwasongwe, Stanford; Norwood, Arnita F.; Sims, Mario; Wang, Wei; Winters, Karen P.; Correa, Adolfo
Abstract : Background: Black persons have an excess burden of cardiovascular disease (CVD) compared with white persons. This burden persists after adjustment for socioeconomic status and other known CVD risk factors. This study evaluated the CVD burden and the socioeconomic gradient of CVD among black participants in the JHS (Jackson Heart Study). Methods and Results: CVD burden was evaluated by comparing the observed prevalence of myocardial infarction, stroke, and hypertension in the JHS at baseline (2000–2004) with the expected prevalence according to US national surveys during a similar time period. The socioeconomic gradient of CVD was evaluated using logistic regression models. Compared with the national data, the JHS age‐ and sex‐standardized prevalence ratios for myocardial infarction, stroke, and hypertension were 1.07 (95% CI, 0.90–1.27), 1.46 (95% CI, 1.18–1.78), and 1.51 (95% CI, 1.42–1.60), respectively, in men and 1.50 (95% CI, 1.27–1.76), 1.33 (95% CI, 1.12–1.57), and 1.43 (95% CI, 1.37–1.50), respectively, in women. A significant and inverse relationship was observed between socioeconomic status and CVD within the JHS cohort. The strongest and most consistent socioeconomic correlate after adjusting for age and sex was income for myocardial infarction (odds ratio: 3.53; 95% CI, 2.31–5.40) and stroke (odds ratio: 3.73; 95% CI, 2.32–5.97), comparing the poor and affluent income categories. Conclusions: Except for myocardial infarction in men, CVD burden in the JHS cohort was higher than expected. A strong inverse socioeconomic gradient of CVD was also observed within the JHS cohort.